Publisher Correction: Dissociating implicit and explicit ensemble representations reveals the limits of visual perception and the richness of behaviour - Sabrina Hansmann-Roth; Árni Kristjánsson; David Whitney; Andrey Chetverikov (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.